Não estou entendendo essa matéria ( pergunta) , algum pode me ajudar ?
Anexos:
![](https://pt-static.z-dn.net/files/d2b/b3121e0afe4cfbf62638e4769196ed96.jpg)
Soluções para a tarefa
Respondido por
0
Boa noite Stephany
E = (2x² - 3y + z)/(y² - 1)
x = -2
y = -3
z = -5
E = (2*(-2)² - 3*(-3) - 5)/((-3)² - 1)
E = (8 + 9 - 5)/(9 - 1)
E = 12/8 = 3/2
E = (2x² - 3y + z)/(y² - 1)
x = -2
y = -3
z = -5
E = (2*(-2)² - 3*(-3) - 5)/((-3)² - 1)
E = (8 + 9 - 5)/(9 - 1)
E = 12/8 = 3/2
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás